Fighting Gender Equality under the Pandemic. The Case of Polish and Hungarian Anti-Gender Equality and Anti-LGBTQ+ Policies under the COVID-19 Crisis - Szelewa, Dorota; Szikra, Dorottya (PARTECIPAZIONE E CONFLITTO, 2024)
The COVID-19 pandemic created a public health, economic and social crisis that had to be handled by states capable of holding tight such societal processes. During this period, right-wing politicians have initiated discourses and policies that portray enemies not related to the virus but to various minorities and oppressed social groups, including women and sexual minorities, and offered exclusionary policies as 'remedies' against these imaginary threats. This paper compares such anti-gender and anti-LGBTQ+ policies in Poland and Hungary under the COVID-19 pandemic and asks: How have right-wing populist leaders in Poland and Hungary utilised the crisis to issue anti-gender equality and anti-LGBTQ+ legislation? What are the main commonalities and differences between the adopted policies and the reactions? In answering these questions, we argue that the governments of two East-Central European EU-member states, Poland and Hungary, with severely weakened democratic institutions, utilised the momentum of the crisis to restrict women's rights and the rights of sexual minorities, playing on gendered nationalist sentiments of the protection of the nation.